2020
DOI: 10.1111/sum.12556
|View full text |Cite
|
Sign up to set email alerts
|

Soil microstructure alterations induced by land use change for sugarcane expansion in Brazil

Abstract: Land use change (LUC) alters soil structure and, consequently, the functions and services provided by these soils. Conversion from extensive pasture to sugarcane is one of the largest land transitions in Brazil as a result of the growth of the domestic and global demands of bioenergy. However, the impacts of sugarcane expansion on the soil structure under extensive pasture remains unclear, especially when considering changes at the microscale. We investigated whether LUC for sugarcane cultivation impacted soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
2
14
0
3
Order By: Relevance
“…First, conventional soil tillage used at land conversion breaks soil aggregates [39], leading to increased soil C oxidation to the atmosphere [38,40]. Secondly, after conversion of external drivers such as soil compaction due to continuous cattle trampling, this negatively influences the soil structure [9,17], water movement [10], and consequently, important ecosystem services, such as grass productivity, soil biodiversity and C sequestration [11], and erosion control. Therefore, the poor soil structure in PA and reduced vegetation cover in poorly managed pastures make the soil more susceptible to runoff [41] and soil erosion [39], mainly in months with higher precipitation, i.e., from October to March in the studied region (Figure 1).…”
Section: Land Transition From Native Vegetation To Pasturementioning
confidence: 99%
“…First, conventional soil tillage used at land conversion breaks soil aggregates [39], leading to increased soil C oxidation to the atmosphere [38,40]. Secondly, after conversion of external drivers such as soil compaction due to continuous cattle trampling, this negatively influences the soil structure [9,17], water movement [10], and consequently, important ecosystem services, such as grass productivity, soil biodiversity and C sequestration [11], and erosion control. Therefore, the poor soil structure in PA and reduced vegetation cover in poorly managed pastures make the soil more susceptible to runoff [41] and soil erosion [39], mainly in months with higher precipitation, i.e., from October to March in the studied region (Figure 1).…”
Section: Land Transition From Native Vegetation To Pasturementioning
confidence: 99%
“…Previous studies indicated that changes in soil uses from native plants to pasture to sugarcane plantation degraded soil microstructure, decreased soil porosity and negatively affected soil pores and particle size distribution, regardless of soil texture and the environmental conditions of the investigated regions (Canisares, et al, 2020). It is well confirmed that land use changes (LUC) alter soil structure and texture and accordingly, soil functionalities and services (Canisares, et al, 2020;Jimenez et al, 2020). The shift from extensive pasture to sugarcane production is one of the largest land-based shifts in Brazil because of the growth of the global and national needs of biofuels.…”
Section: Effects Of Long-term Sugarcane Monoculture On Some Soil Physical Propertiesmentioning
confidence: 94%
“…The shift from extensive pasture to sugarcane production is one of the largest land-based shifts in Brazil because of the growth of the global and national needs of biofuels. Hence, largescale land use changes (LUC) to expand sugarcane production in Brazil have reduced soil microporosity, regardless of the site-specific conditions and soil type, signifying that implementation of more reliable management practices is imperious to preserve soil structure and sustain soil health in sugarcane fields (Canisares, et al, 2020;Jimenez et al, 2020;.…”
Section: Effects Of Long-term Sugarcane Monoculture On Some Soil Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was especially marked following the addition of glucose, which elevated the rate of microbial respiration. It is also possible to gain some insight into soil structure by dissecting and analysing cross/thin sections of soil [7] . Thin sections are typically obtained by impregnating a soil with synthetic resin and then cutting with a diamond-tipped blade following a curing period prior to polishing.…”
Section: Recent Methods For Investigating Microbial (Micro)environmenmentioning
confidence: 99%